Application of Flexible Multibody Systems in Modelica for the Simulation of Construction Machinery - Starke, Martin; Garbe, Robin; Waurich, Volker; Will, Frank (Center for Model-Based Cyber-Physical Product Development, 2021)
Supporting structures of construction machines deform due to heavy process loads, vibration or lightweight design. This causes disturbances in forward kinematic sensing and calculation for end-effector positioning. Furthermore, it effects the transfer behaviour, which is relevant in vibration analysis. System simulations using Modelica are a feasible approach to analyse mechanics, hydraulics and process-interaction of mobile machines. In order to consider the effect of deformation, flexible bodies have to be modeled. This paper describes the workflow for modeling flexible bodies based on a model order reduction in an FEM-software. The reduced model is exported as a standardized SID-file by an open-source SID-generator. The SID-file is used to initialize a flexible body in the open-source Modelica library EMBSlib. For the example of a tandem roller and a boom lift, the application of flexible bodies is presented.